Study of the dense molecular gas surrounding the ‘extended green object’ G35.03+0.35 - Paron, Sergio Ariel (2012)
We present the results of a new study of the molecular gas associated with the ´extended green object´ (EGO) G35.03+0.35. This object, very likely a massive young stellar object, is embedded in a molecular cloud at the border of an H II region. The observations were performed with the Atacama Submillimeter Telescope Experiment in the 12CO and 13CO J= 3-2, HCO+ J= 4-3 and CS J= 7-6 lines with an angular resolution of about 22 arcsec. From the 12CO J= 3-2 line, we discovered outflowing activity of the massive young stellar object. We obtained a total mass and kinetic energy for the outflows of 30 and 3000 Msun (km s-1)2 (6 × 1046 erg), respectively. We discovered an HCO+ and CS clump towards the EGO G35.03+0.35. The detection of these molecular species supports the presence of molecular outflows and a dense molecular envelope with temperatures and densities above 40 K and 6 × 106 cm-3, respectively. Using public near- and mid-infrared and submillimetre data, we investigated the spectral energy distribution confirming that EGO G35.03+0.35 is a massive young stellar object at its earliest evolutionary stage (i.e. a class I young stellar object). By analysing radio-continuum archival data, we found three radio sources towards the object, suggesting the presence of several young stellar objects in the region. Our radio-continuum analysis is consistent with the presence of at least one ultracompact H II region and a hypercompact H II region or a constant-velocity ionized wind source.